(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The article highlights the optimal calculation methods for determining the parameters of heat and mass transfer processes occurring in the rotary-vane engine with an external supply of heat. It is shown that the mathematical model of working processes must consist of two parts. One part describes the processes occurring in the isolated volume. The second part describes the processes of mass exchange between the working chambers of two modules, as well as a heater or a cooler.